Effects of a Vancomycin-Rifampin Combination on Enterococci - Watanakunakorn, Chatrchai (1982)
By the time-kill curve method, a vancomycin-rifampin combination showed neither synergism nor antagonism against 43 of 48 strains of enterococci. Antagonism was demonstrated against five strains.